PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Albab, Muhammad Ulul; Sudiro, Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Companies must consider many factors in an effort to improve employee performance which includes salary, organizational culture, leadership, work discipline, job satisfaction, work motivation, and work environment. The objective of this research is to identify the effects of work motivation and workplace environtment on the performance of employees of PT. World Innovative Telecommunication (OPPO) Malang. This quantitative research uses descriptive analysis and multiple linear regression performed in IBM SPSS. The independent variable is work motivation (X1) and workplace environtment (X2), while the dependent variable is employee performance (Y). the results of the hypothesis testing indicate that work motivation and workplace environtment simultaneously affect employee performance, that work motivation partially has a significant and positive influence on employee performance, and that workplace environtment partially has a significant and positive effect on employee performance.